2014
DOI: 10.1152/ajpregu.00138.2014
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-dependent insulin modulation of synaptic inhibition in neurons of the dorsal motor nucleus of the vagus is altered in diabetic mice

Abstract: Pathologies in which insulin is dysregulated, including diabetes, can disrupt central vagal circuitry, leading to gastrointestinal and other autonomic dysfunction. Insulin affects whole body metabolism through central mechanisms and is transported into the brain stem dorsal motor nucleus of the vagus (DMV) and nucleus tractus solitarius (NTS), which mediate parasympathetic visceral regulation. The NTS receives viscerosensory vagal input and projects heavily to the DMV, which supplies parasympathetic vagal moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…Subsets of these neurons, and GABA neurons in particular, are known to be glucose-sensitive (Oomura et al, 1974, Balfour et al, 2006, Wan and Browning, 2008, Browning, 2013, Lamy et al, 2014, Boychuk et al, 2015a). Several physiological aspects of central vagal circuitry are altered functionally in diabetes (Zsombok et al, 2011, Browning, 2013, Blake and Smith, 2014, Bach et al, 2015, Boychuk et al, 2015b), consistent with modified parasympathetic regulation of the viscera concurrent with the disease (Saltzman and McCallum, 1983). Glucose sensing in NTS neurons involves GCK, which catalyzes the conversion of glucose to glucose-6 phosphate in neurons and other cells (Balfour et al, 2006, Briski et al, 2009), resulting in increased ATP/ADP ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsets of these neurons, and GABA neurons in particular, are known to be glucose-sensitive (Oomura et al, 1974, Balfour et al, 2006, Wan and Browning, 2008, Browning, 2013, Lamy et al, 2014, Boychuk et al, 2015a). Several physiological aspects of central vagal circuitry are altered functionally in diabetes (Zsombok et al, 2011, Browning, 2013, Blake and Smith, 2014, Bach et al, 2015, Boychuk et al, 2015b), consistent with modified parasympathetic regulation of the viscera concurrent with the disease (Saltzman and McCallum, 1983). Glucose sensing in NTS neurons involves GCK, which catalyzes the conversion of glucose to glucose-6 phosphate in neurons and other cells (Balfour et al, 2006, Briski et al, 2009), resulting in increased ATP/ADP ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Type I diabetes is characterized by uncontrolled hyperglycemia due to reduced insulin secretion from pancreatic beta cells. Synaptic and other cellular responses in the dorsal vagal complex are altered in models of type 1 diabetes, even after normalizing glucose concentration (Zsombok et al, 2011, Browning, 2013, Blake and Smith, 2014, Bach et al, 2015, Boychuk et al, 2015b). Vagal reflexes are often blunted during chronic hyperglycemia, and altered vagal function may contribute to diabetes-associated visceral dysfunction (Saltzman and McCallum, 1983, Undeland et al, 1998), suggesting that chronically-elevated glucose alters responsiveness of neurons in the dorsal vagal complex.…”
Section: Introductionmentioning
confidence: 99%
“…Subsets of these neurons, and GABA neurons in particular, are known to be glucose-sensitive , Balfour et al, 2006, Wan and Browning, 2008, Browning, 2013, Lamy et al, 2014, Boychuk et al, 2015a. Several physiological aspects of central vagal circuitry are altered functionally in diabetes (Zsombok et al, 2011, Browning, 2013, Blake and Smith, 2014, Bach et al, 2015, Boychuk et al, 2015b, consistent with modified parasympathetic regulation of the viscera concurrent with the disease (Saltzman and McCallum, 1983). Glucose sensing in NTS neurons involves GCK, which catalyzes the conversion of glucose to glucose-6 phosphate in neurons and other cells (Balfour et al, 2006, Briski et al, 2009, resulting in increased ATP/ADP ratio.…”
Section: Discussionmentioning
confidence: 99%
“…This model involves injecting animals systematically with STZ, which kills the insulin-producing pancreatic β-cells, resulting in chronic hyperglycemia in conjunction with hypoinsulinemia (Craighead 1980). These studies revealed that chronically increased blood glucose concentrations in the STZ model of type 1 diabetes is accompanied by altered neurotransmitter function in the DVC (Bach et al 2015;Blake and Smith 2014;Boychuk et al 2015b;Zsombok et al 2011). These effects persisted for hours (at least) after glucose was standardized to control levels in vitro.…”
Section: Energy Homeostasis In the Dvc And Pathological Consequencesmentioning
confidence: 99%
See 1 more Smart Citation